2004
DOI: 10.1007/s00240-003-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Penile apoptosis in association with p53 under lack of testosterone

Abstract: It is known that testosterone deficiency induces apoptosis in the prostate and that p53 protein is involved in this apoptosis. Therefore, p53 protein may also be involved in apoptosis induction in a testosterone-deficient state in the penis. In this study, we investigated whether castration and chemical castration induce apoptosis at penile tissue in rats, and whether p53 protein is involved in this apoptosis. Male SD rats aged 8 weeks were divided into four groups: 1) the Control group; 2) the Castration grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…This report suggested that low plasma testosterone levels were associated with EDys in men, independently of the presence of other VRFs, corroborating the idea that testosterone has a protective effect in endothelial functionality [32]. At penile level, studies in animal models suggested that testosterone deficiency is associated to apoptosis of cavernosal vascular ECs [48] and that testosterone replacement therapy was able to induce CC cell proliferation and endothelial DNA synthesis [49]. Additionally, testosterone has been suggested to modulate several pathways on different erectile tissue components crucial for normal erection.…”
Section: Testosterone Endothelial Health and Erectionmentioning
confidence: 52%
“…This report suggested that low plasma testosterone levels were associated with EDys in men, independently of the presence of other VRFs, corroborating the idea that testosterone has a protective effect in endothelial functionality [32]. At penile level, studies in animal models suggested that testosterone deficiency is associated to apoptosis of cavernosal vascular ECs [48] and that testosterone replacement therapy was able to induce CC cell proliferation and endothelial DNA synthesis [49]. Additionally, testosterone has been suggested to modulate several pathways on different erectile tissue components crucial for normal erection.…”
Section: Testosterone Endothelial Health and Erectionmentioning
confidence: 52%
“…For experiment 1, the animals were injected subcutaneously with either 0.9% saline (vehicle; Sigma-Aldrich, St. Louis, MO) or LEU (1.2mg/kg; Sigma-Aldrich, St. Louis, MO) thirty minutes before the extinction session on day 2. The 1.2mg/kg dose was selected based on results from our dose response test to confirm this was the lowest dose to induce the T surge, as well as previous reports examining the castration effects of LEU with chronic administration at doses from 1–3mg/kg for days to months (Ichikawa et al, 1988; Kostanski et al, 2000; Yamamoto et al, 2004). On day 3 for both experiments, the animals were returned to the chamber and presented with 3 CS-alone trials for the extinction recall test.…”
Section: Methodsmentioning
confidence: 99%
“…A remodeling process occurs in the penis of castrated rats that involves apoptosis of the erectile tissue [20–23]. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%